Knowledge Organization in the Intersection with Information Technologies - Martinez-Avila, Daniel [UNESP] (Ergon-verlag, 2015)
This paper analyzes the historical role and possibilities of knowledge organization (KO) in relation to information technologies (IT). Different moments in history that are analyzed include the development of the Internet, the World Wide Web, the Semantic Web, problems of artificial intelligence, Web 2.0, and linked (open) data. The paper concludes with the analysis of some IT applications, challenges and opportunities in which KO theory and fundamentals might play a key role in the new environment, as well as the transformation of the field.
Keywords: World Wide Web; knowledge organization; data; information technologies; Semantic Web; artificial intelligence